Efecto de las histonas en la sobrevida y actividad angiogénica de células endoteliales maduras y progenitores endoteliales - Mena, Hebe Agustina (2017)
Extracellular histones are derived from dead cells or from extracellular neutrophil traps. In sites of tissue injury and inflammation, histone levels are high and remain elevated during tissue regeneration, stage in which endothelium is a key player in the formation of new blood vessels. Although the cytotoxic effect of histones has been demonstrated in mature endothelial cells, the aim of this thesis is to extend these findings by clarifying the mechanisms involved. Also, we aimed to study the action of histones on endothelial progenitor cells such as endothelial colony forming cells (ECFC), which increase locally in response to injury due to migration from the bone marrow. Our results show that human recombinant histones H2B, H3 and H4 induce the death of human late outgrowth endothelial progenitor cells and mature endothelial cells from macro and microvessels, promoting both apoptosis and pyroptosis. Using non-cytotoxic concentrations, we observed that H2B, H3 and H4 inhibited various angiogenic responses including proliferation, migration and vessel formation both in vitro and in vivo. The cytotoxic and antiangiogenic effects of histones were completely suppressed by heparin and mainly mediated by the endothelial receptors TLR2 and TLR4. In conclusion, histones induce apoptosis and pyroptosis of ECFC and mature endothelial cells and inhibit their angiogenic functions. The fact that histone-mediated cytotoxic and antiangiogenic effects disappear in the presence of heparin or TLR2 and TLR4 neutralizing antibodies suggests the use of these compounds as a therapeutic strategy to improve tissue regeneration.